1999
DOI: 10.1074/jbc.274.13.8958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epidermal Growth Factor Receptor Internalization on Regulation of the Phospholipase C-γ1 Signaling Pathway

Abstract: The epidermal growth factor receptor (EGFR) ligands, epidermal growth factor (EGF), and transforming growth factor-␣ (TGF␣) elicit differential postendocytic processing of ligand and receptor molecules, which impacts long-term cell signaling outcomes. These differences arise from the higher affinity of the EGF-EGFR interaction versus that of TGF␣-EGFR in the acidic conditions of sorting endosomes. To determine whether EGFR occupancy in endosomes might also affect short-term signaling events, we examined activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 49 publications
(45 reference statements)
6
97
0
Order By: Relevance
“…Several recent studies (60,61) have demonstrated that changes in phosphoinositide levels, specifically PIP 2 , and concomitant changes in the actin dynamics are essential to some cell surface events including motility. In fact, peptides encompassing the PIP 2 binding domain of an actin-binding protein of the villin superfamily (gelsolin) have been shown to increase cell motility in fibroblasts (62).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies (60,61) have demonstrated that changes in phosphoinositide levels, specifically PIP 2 , and concomitant changes in the actin dynamics are essential to some cell surface events including motility. In fact, peptides encompassing the PIP 2 binding domain of an actin-binding protein of the villin superfamily (gelsolin) have been shown to increase cell motility in fibroblasts (62).…”
Section: Discussionmentioning
confidence: 99%
“…Surface Titration Protocol-This stimulation procedure allows the numbers of activated EGFR at the plasma membrane and in intracellular compartments following endocytosis to be varied independently, as described previously (32) and illustrated in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Lysates were clarified by centrifugation, diluted to various extents in blocking buffer supplemented with 1 mM sodium orthovanadate, and incubated in the antibody-coated wells for 1 h at 37°C. The amount of associated phosphotyrosine was determined using alkaline phosphatase-conjugated RC20 anti-phosphotyrosine antibody (Transduction Laboratories) and p-nitrophenyl phosphate (Sigma) substrate as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations